Temporal lobectomy: long-term seizure outcome, late recurrence and risks for seizure recurrence - McIntosh, Anne M.; Kalnins, Renate M.; Mitchell, L. Anne; Fabinyi, Gavin C. A.; Briellmann, Regula S.; Berkovic, Samuel F. (Brain (London, England : 1878), 2004)
There is little information available relevant to long-term seizure outcome after anterior temporal lobectomy, particularly at extended postoperative periods. The aim of this study was an in-depth examination of patterns of longitudinal outcome and potential risk factors for seizure recurrence after lobectomy, utilizing a large patient sample with long follow-up. Included were 325 patients who underwent anterior temporal lobectomy between 1978 and 1998 (mean follow-up 9.6 ± 4.2 years). Retrospective data were analysed using survival analysis and multivariate regression with Cox proportional hazard models. The probability of complete seizure freedom at 2 years post-surgery was 55.3% [95% confidence interval (CI) 50–61]; at 5 years, 47.7% (95% CI 42–53); and at 10 postoperative years it was 41% (95% CI 36–48). Patients with discrete abnormalities preoperatively (i.e. lesions and hippocampal sclerosis) had a significantly higher probability of seizure freedom than patients without obvious abnormality. The latter group had a pattern of recurrence similar to that in patients with lesions outside the area of excision. After adjustment for preoperative pathology, only the presence of preoperative secondarily generalized seizures had a significant association with recurrence [occasional preoperative generalized seizures, hazard ratio (HR) 1.6, 95% CI 1.1–2.3; frequent seizures, HR 2.0, 95% CI 1.4–2.9 compared with absence of preoperative generalized seizures]. Duration of preoperative epilepsy, age of seizure onset and age at surgery did not have an effect on outcome. Patients with two seizure-free postoperative years had a 74% (95% CI 66–81) probability of seizure freedom by 10 postoperative years. This late seizure recurrence was not associated with any identified risk factors. Specifically, patients with hippocampal sclerosis were not at higher risk. Surprisingly, complete discontinuation of anti-epileptic drugs (AEDs) after two postoperative years was not associated with an increased risk of recurrence (HR 1.03, 95% CI 0.5–2.1). This may be because selection of patients for AED discontinuation is biased towards those individuals perceived as ‘low risk’. The results of this study indicate that the lack of an obvious abnormality or the presence of diffuse pathology, and preoperative secondarily generalized seizures are risk factors for recurrence after surgery. Late recurrence after initial seizure freedom is not a rare event; risk factors specific to this phenomenon are as yet unidentified.